Hazai pezsgőpiac a Törley Pezsgőpincészet-Pezsgőmanufaktúra szemszögéből - Kanyár László (2018)
The purpose of my essay is to show the actual situation of Törley champagne cellar in Hungary, beginning from the history and development of the process of champagne production till the wide variety of champagne in the shops people can choose from in our days in Hungary. I would like to reveal how the culture of champagne consumption is developing and how champagne has become a typical sign of Hungary. I would like to show why marketing has a big importance in the operation of a company, and how these marketing ideas are used in Törley cellar’s practice. I think it is important to emphasize the importance of the visitor centre and why the company wants to maintain it for it’s operation. Based on these information I set up a questionnaire as a tool of my survay to study which people drink champagne, at what ocassion they do, whether they are involved in the processes of production, what knowledge they have about hungarian brands and the value of them. By summerizing these data I recognized which people are everyday customers and which consider champagne as the drink of unique occasion. One of the main purpuses of Törley champagne cellar is to achieve that champagne becomes the drink of our everydays and not just festive accessory of special occasions, in a normal way of consumption of course. Based on the results of my survay I am happy to see that Törley has a monarchy in Hungary among champagne brands. That is the reason why I think it has a significance that Törley shows the advantages of this fine drink from different aspects as well.